66.8k views
1 vote
Can someone help me figure out how to solve this problem

Can someone help me figure out how to solve this problem-example-1
User RunHolt
by
5.2k points

1 Answer

3 votes

Answer:


r = (3)/(4)

Explanation:

Geometric sequence formula:
a_n = a_1 r^(n-1)

From the provided sequence, we know that the first term is -4

The second term is -3

Inserting to value to the formula

( n = 2, since we are using the value of the second term)


a_2 = -4 * r^(2-1)\\


-3 = -4 * r


r = (-3)/(-4)


r = (3)/(4)

User Astoria
by
5.2k points